From Strategy to Strategic Agility - Abd Rahman Ahmad; Mohammed Alzoraiki (2023)
In the contemporary business world, the robustness of an organization is crucial as the business environment is very complex and uncertain. The growth and development of an organization heavily depend on internal and external factors. Therefore, it is imperative to find an effective and optimal way to confront this change with the emergence of strategic agility. Agility is considered indispensable for all organizations operating in a rapidly growing or turbulent environment. Here, the application of strategic agility in organizations requires the availability of leaders with high efficiency and skills, as well as knowledge and capability to organize the organizational structure that allows for collaboration between the various levels of the organization. These will facilitate a supportive, careative and innovative organizational climate. Thus, the swift response ensures the organization to remain competitive or sustains its business operations effectiveness. Therefore, the organization must have strategic sensitivity, collective commitment and ensure the flow of resources is able to be fully employed.